The Host Galaxy of FRB 20190520B and Its Unique Ionized Gas Distribution - Xiang-Lei Chen; Chao-Wei Tsai; Daniel Stern; Christopher D. Bochenek; Shami Chatterjee; Casey Law; Di Li; Chen-hui Niu; Yuu Niino; Yi Feng; Pei Wang; Roberto J. Assef; et al. (The Astrophysical Journal)
The properties of host galaxies associated with fast radio bursts (FRBs) provide critical information for inferring the progenitors and radiation mechanisms of these bursts. We report on the host galaxy of the repeating FRB 20190520B, a dwarf galaxy at the spectroscopic redshift z = 0.241 with a stellar mass of (6.2 ± 0.8) × 10 ^8 M _⊙ . The emission-line ratios suggest that the ionized gas is powered by star formation. The total H α -traced star formation rate (SFR) is 0.70 ± 0.01 M _⊙ yr ^−1 , and the metallicity is $12+{{\rm{log}}}_{10}([{\rm{O}}/{\rm{H}}])\geqslant 7.4\pm 0.1$ . The specific star formation rate (sSFR) is ${\rm{log}}\,{{\rm{sSFR/yr}}}^{-1}=-9.0\pm 0.1$ , higher than the upper limit of −9.4 observed in nearby dwarf galaxies. The dispersion measure (DM) contribution from the host galaxy is estimated to be DM _host ≈ 950 ± 220 pc cm ^−3 , based on the H α emission. The FRB and the associated persistent radio source are located at the H α emission peak, offset by ∼1 $\mathop{.}\limits^{{\rm{^{\prime} }}}$ 4 (5.5 kpc) in projection from the stellar continuum. At this position, the lower limit of $\mathrm{log}\,\mathrm{sSFR}/{\mathrm{yr}}^{-1}$ is −8.5 ± 0.1, more than 3 times the galaxy’s total sSFR. The H α velocity difference between the stellar continuum and the offset gas is 39.6 ± 0.4 km s ^−1 , which is sufficient to draw conclusions about the nature of the offset.